Cover Image. Issue 4 (10th May 2021) - Wang, Yuelin; Yu, Miao; Hu, Bojie; Jin, Xuemin; Li, Yibin; Zhang, Xiao; Zhang, Yongpeng; Gong, Di; Wu, Chan; Zhang, Bilei; Yang, Jingyuan; Li, Bing; et al.
Abstract : The cover image is based on the Research Article Deep learning‐based detection and stage grading for optimising diagnosis of diabetic retinopathy by Yuelin Wang et al., https://doi.org/10.1002/dmrr.3445 .